PENGARUH KOMUNIKASI INTERPERSONAL DAN PEMANFATAAN TEKONOLOGI INFORMASI TERHADAP KUALITAS PELAYANAN PASPOR DI KANTOR IMIGRASI KELAS I KHUSUS NON TPI JAKARTA SELATAN - Mulyawan, Budy; Firlana, Habbi; Kristi Wibowo, Pascalis Danny; Mastur, Anida Sri Rahayu; Adillah, Muhammad Arief; Widayat, Wisnu (JURNAL LENTERA BISNIS, 2026)
Along with the increasing use of social media as a means of public communication, the direct role of interpersonal communication between officers and the public remains an essential element in providing quality services. This phenomenon has become a real public concern, especially at the South Jakarta Special Class I Non-TPI Immigration Office, regarding the quality of interpersonal communication demonstrated by immigration officers during the passport application interview process. The objectives of this study are as follows: 1) To analyze the influence of immigration officers' interpersonal communication at the South Jakarta Special Class I Non-TPI Immigration Office on the quality of passport services; 2) To analyze the influence of information technology utilization at the South Jakarta Special Class I Non-TPI Immigration Office on the quality of passport services; 3) To analyze the combined influence of immigration officers' interpersonal communication and information technology utilization on the quality of passport services at the Immigration Office. This study uses a quantitative method with a survey approach to analyze the relationship between interpersonal communication variables, information technology utilization, and passport service quality. The t-test results for the second model obtained a significance value for the Interpersonal Communication variable of 0.000 (t = 4.953). The Information Technology variable was 0.000 (t = 14.361). The F-test results for the second model obtained a calculated F value of 1004.211 with a significance value of 0.000, which is smaller than α = 0.05.